1990
DOI: 10.1093/jaoac/73.6.842
|View full text |Cite
|
Sign up to set email alerts
|

Fluorometric Determination of Alkaline Phosphatase in Fluid Dairy Products: Collaborative Study

Abstract: Official methods for the measurement of alkaline phosphatase (ALP) in dairy products use either phenyl phosphate or phenolphthaleln monophosphate as substrate. Quantitation of results requires butanol extraction of the Indophenol (Scharer) or 3-h dialysis of the liberated phenolphthaleln (Rutgers). The Advanced Fluorophos® assay Is based on a self-indicating substrate which, when acted upon by ALP, loses a phosphate radical and becomes a highly fluorescent compound. The rate of fluorophore formation Is monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…For Fluorophos, these ranged between 0.9% and 7.5% and for the A&M procedure between 3.5% and 29%. These values compare favourably with reported data (Rocco 1990; Harding and Garry 2005).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…For Fluorophos, these ranged between 0.9% and 7.5% and for the A&M procedure between 3.5% and 29%. These values compare favourably with reported data (Rocco 1990; Harding and Garry 2005).…”
Section: Resultssupporting
confidence: 91%
“…At higher raw milk additions (500–2000 mU/L equivalent), although the results were not in the expected ranges, good repeatability was achieved with mean RSD r values between 4.4% and 8.8% (Table 1). This compares favourably with values in the literature for this procedure (Rocco 1990; Scintu et al. 2000).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Research has recently led to the reduction of the maximum residual limiting rade Aproducts to 350mU/L (Painter and Bradley, [39]; International Dairy Federation,1999) found less than 150mU/Lof ALP activity in under pasteurized low fat milk. In a collaborative study with a fluorometric assay, Rocco [87] found that milk contaminated with as much as 0.5% raw milk showed less than 265mU/L of ALP activity, there by stressing the need to reconsider current regulatory standards. An additional study (Klotz [56]) on cow, goat and sheep milks also suggests that the present limit of 350mU/L can be reduced further given that raw goat milk ALP levels were<350mU/L.…”
Section: Discussionmentioning
confidence: 99%